2006
DOI: 10.1098/rspb.2006.3733
|View full text |Cite
|
Sign up to set email alerts
|

Spread of arbitrary conventions among chimpanzees: a controlled experiment

Abstract: Wild chimpanzees (Pan troglodytes) have a rich cultural repertoire-traditions common in some communities are not present in others. The majority of reports describe functional, material traditions, such as tool use. Arbitrary conventions have received far less attention. In the same way that observations of material culture in wild apes led to experiments to confirm social transmission and identify underlying learning mechanisms, experiments investigating how arbitrary habits or conventions arise and spread wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 33 publications
(34 reference statements)
2
100
1
Order By: Relevance
“…In a recent study on translocation events of zoo chimpanzees (which mimics the immigration events in the wild), it was found that the immigrating individuals conform to vocalization pattern of their new group [81]. Studies in captivity have shown that adjustments based on the desire to create or maintain a positive group sense might exist in chimpanzees [64,65,82,83]. Adjusting behaviour potentially could reduce differences between the local group member and the immigrant and favour acceptance into the group.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on translocation events of zoo chimpanzees (which mimics the immigration events in the wild), it was found that the immigrating individuals conform to vocalization pattern of their new group [81]. Studies in captivity have shown that adjustments based on the desire to create or maintain a positive group sense might exist in chimpanzees [64,65,82,83]. Adjusting behaviour potentially could reduce differences between the local group member and the immigrant and favour acceptance into the group.…”
Section: Discussionmentioning
confidence: 99%
“…Starting with one skilled individual (natural invention or trained skill), the rest of the group acquires the same particular way of behaving by means of social learning (Hopper et al, 2011;Perry, 2009;Whiten et al, 2005). On the other hand, the label 'conformity' has been used to describe the process by which primates would revert back to the majority strategy after discovering an alternative strategy (chimpanzees: Bonnie et al, 2007;Hopper et al, 2011;Whiten et al, 2005;capuchin monkeys: Dindo et al, 2008capuchin monkeys: Dindo et al, , 2009). Here, after socially acquiring a particular way of behaving, some individuals would occasionally explore an alternative strategy, but then change back to preferring the majority strategy.…”
Section: Do Primates Show Conformity?mentioning
confidence: 99%
“…In recent years, majority influence has become a favourable research topic for behavioural biologists. One line of research has focused on our closest living relatives, the nonhuman primates (chimpanzees, Pan troglodytes: Bonnie, Horner, Whiten, & de Waal, 2007;Haun, Rekers, & Tomasello, 2012;Hopper, Schapiro, Lambeth, & Brosnan, 2011;Whiten, Horner, & de Waal, 2005; capuchin monkeys, Cebus apella: Dindo, Thierry, & Whiten, 2008;Dindo, Whiten, & de Waal, 2009;Perry, 2009), which could enable intriguing analysis of the evolutionary roots of this human phenomenon (MacLean et al, 2012). Another line of research has aimed to investigate the possibility of convergent evolution of conformity by focusing on phylogenetically more distant species, such as fish (Day, MacDonald, Brown, Laland, & Reader, 2001;Kendal, Coolen, & Laland, 2004;Pike & Laland, 2010), rats (Galef & Whiskin, 2008;Jolles, de Visser, & van den Bos, 2011;Konopasky & Telegdy, 1977) and fruit flies (Battesti, Moreno, Joly, & Mery, 2012).…”
mentioning
confidence: 99%
“…They are characterized 225 by a functional and goal-directed task and constitute efficient means to achieve physical ends; 226 for example, termites must be extracted from their mound to be eaten. Thus, chimpanzees 227 most certainly do not use specific tools because everybody else does so, although this might 228 be the case for an individual's first use of a tool, but because after some experience they 229 understand the utility and effectiveness of the practice (Bonnie et al 2007;Turiel 1983). 230…”
Section: Level 173mentioning
confidence: 99%